2014
DOI: 10.1038/pcan.2014.28
|View full text |Cite
|
Sign up to set email alerts
|

Imaging, procedural and clinical variables associated with tumor yield on bone biopsy in metastatic castration-resistant prostate cancer

Abstract: Background-Understanding the mechanisms driving disease progression is fundamental to identifying new therapeutic targets for the treatment of men with metastatic castration-resistant prostate cancer (mCRPC). Due to the prevalence of bone metastases in mCRPC, obtaining sufficient tumor tissue for analysis has historically been a challenge. In this exploratory analysis, we evaluated imaging, procedural, and clinical variables associated with tumor yield on imageguided bone biopsy in men with mCRPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 12 publications
3
37
4
Order By: Relevance
“…Thus, a large proportion of patients do not have soft tissue metastases amenable for biopsy. A number of studies published in the past decade have reported variable rates of positive BMBs ranging from 25% to 50% for nonimaging-guided biopsies16, 17, 20 and increasing to 67% to 77% when performed under direct CT guidance 15, 21. Our cohort, with biopsies performed without direct CT guidance, had a bone biopsy positivity rate of 62.5%, consistent with the findings from previous reports.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, a large proportion of patients do not have soft tissue metastases amenable for biopsy. A number of studies published in the past decade have reported variable rates of positive BMBs ranging from 25% to 50% for nonimaging-guided biopsies16, 17, 20 and increasing to 67% to 77% when performed under direct CT guidance 15, 21. Our cohort, with biopsies performed without direct CT guidance, had a bone biopsy positivity rate of 62.5%, consistent with the findings from previous reports.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have established associations among the clinical, analytical, and CT parameters with BMB positivity 16, 21. The present study, however, is the first study to establish the value of the widely used CT and analytical parameters and develop a score with direct applicability in the clinical setting, with validation of these results in a separate control group.…”
Section: Discussionmentioning
confidence: 78%
“…Historically, this process has been a challenge given the paucity of soft tissue metastases and dense sclerotic reaction associated with bone metastases, making biopsies and tissue processing technically difficult resulting in low tumor yield. We previously demonstrated that imaging, procedural, and clinical variables have an impact on image-guided bone biopsy tumor yield and this work demonstrates that bone biopsy in metastatic CRPC is feasible resulting in sufficient tumor yield in 80% of samples for correlative assessment (41). …”
Section: Discussionmentioning
confidence: 88%
“…Metastatic biopsies have been challenged by a predominance of sclerotic bone lesions, which are technically challenging and harbor limited viable tissues for extensive analyses. Nonetheless, in recent years through collaborative efforts and clinical trials, biopsies in metastatic prostate cancer have become feasible [12]. Tumor biopsy programs including those from the Stand Up To Cancer (SU2C)- Prostate Cancer Foundation (PCF) Dream Team clinical trials [13, 14] have revealed 1) genomic diversity between patients with CRPC; 2) acquisition and/or enrichment of molecular alterations in CRPC compared to primary prostate cancer; 3) emergence of pathologic variants including atypical and neuroendocrine phenotypes.…”
Section: Introductionmentioning
confidence: 99%